2012
DOI: 10.3109/0886022x.2012.745115
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype 2 Familial Mediterranean Fever: Evaluation of 22 Case Series and Review of the Literature on Phenotype 2 FMF

Abstract: Familial Mediterranean fever (FMF) is an autosomal recessive autoimmune disorder characterized by recurrent bouts of fever and serosal inflammation. FMF may be complicated by AA-type amyloidosis, worsening the prognosis, with associated renal failure in some patients. Complication rate varies with race, being as high as 60% in Turks and as low as 2% in Armenians. In a few cases of patients with FMF (phenotype 2), amyloid nephropathy may be the presenting manifestation. This study included 420 patients who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…Homozygous p.M694V mutations were significantly higher in patients with AN (8/16; 50.0%) than N-AN (2/14; 14.4%), which was in accordance with the literature (p = 0.045) [20]. However, it is known that there are also mutations other than p.M694V which may lead to amyloidosis as seen in our patients [4,17,[19][20][21][22]. Besides, 2 patients in the N-AN group had homozygous p.M694V mutations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Homozygous p.M694V mutations were significantly higher in patients with AN (8/16; 50.0%) than N-AN (2/14; 14.4%), which was in accordance with the literature (p = 0.045) [20]. However, it is known that there are also mutations other than p.M694V which may lead to amyloidosis as seen in our patients [4,17,[19][20][21][22]. Besides, 2 patients in the N-AN group had homozygous p.M694V mutations.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age at the onset of FMF disease was 7.2 ± 3.0 years, which was in accordance with the literature [18]. In our study, fever was seen in 56.3%, abdominal pain in 56.3%, arthralgia/arthritis in 31.3%, and chest pain in 12.5% of the FMF AN patients, which were lower than those in similar studies, which might have resulted from differences in patient selection [18,19]. The characteristics of FMF attacks at presentation were different in AN and N-AN groups.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, 19 out of 507 FMF patients (3.7%) were homozygous for E148Q in this study. Altunoglu et al 28 demonstrated that the most prevalent allelic variant was M694V followed by E148Q in patients with FMF phenotype II (in phenotype II, isolated amyloidosis is the sole and first manifestation of FMF). In their study group consisting of 22 FMF patients with phenotype II, four were heterozygous for E148Q.…”
Section: Discussionmentioning
confidence: 99%
“…This is a rare presentation of FMF, and treatment is with colchicine. The largest reported series of 22 patients suggests a predominance of M694V homozygote cases [ 100 ], but this is not replicated in all series [ 101 ].…”
Section: Phenotype II Fmfmentioning
confidence: 96%
“…In phenotype II FMF, patients present with amyloid nephropathy either without or before developing any symptomatic FMF attacks [ 100 ]. This is a rare presentation of FMF, and treatment is with colchicine.…”
Section: Phenotype II Fmfmentioning
confidence: 99%